O efeito da interatividade e do suporte técnico na intenção de uso de um sistema de e-learning - Garcia, Rodrigo Antônio (2016)
In the recent years, several researchers are dedicated to study the determining factors for the acceptance or rejection of a particular system by the users. According to Freitas (2009), the using of the computer as a mediator of the interactions in the learning environment, besides to represent the 3rd generation in the technological evolution of the Distance Education (DE), it also enabled the e-learning. Still, according to Freitas (2009), although there is this common point, distance education and e-learning do not mean the same thing. E-learning can be understood as the use of digital technologies in the teaching-learning process, with the Internet as a support and it may be in person or at a distance. This study aimed to identify the variables that influence positively or negatively in the e-learning use acceptance by the students in an undergraduate course at a distance, of a Higher Education Institution (HEI), as a tool for teaching/learning process. From the literature review, it was identified that Davis's (1989) Technology Acceptance Modeling (TAM) would be the most robust for the proposal evaluation. It was apllied a questionnaire, which resulted in a sample of 260 students and the obtained data were analyzed using the Structural Equation Modeling (SEM). The results confirmed the validity of all assumptions. The Planned Relations in the original TAM Modeling were confirmed in this study, as well as the availability of the technical support on the perceived facility of use and the interactivity on the perceived usefulness.